Research on the self-lubricating performance of rolling linear guide based on directional porous media - Haiyong Wu; Na Lin; Yang Chen; Bihua Shen; Li Liu; Erjun Lu; Guosheng Xu; Qiqin Cai (Scientific Reports)
Abstract Self-lubricating rolling linear guides are high value-added, maintenance-free rolling functional components. In this article, a porous media with a directional pore structure is prepared by PTFE and pore forming agent naphthalene, the design of the slider end structure is optimized, and the oil film thickness of the rolling linear guide under different operating speeds, loads, and operating mileage are tested and tracked by a spectrometer to provide a comprehensive analysis of the self-lubricating performance of the rolling linear guide. The research results indicate that the oil film thickness is directly proportional to the slider operating speed, while the effects of load and operating mileage on the oil film thickness are not significant. The oil storage rate shows an inverse relationship with the operating mileage. The interconnected pores within the porous media demonstrate good directionality, and the porous oil storage media can achieve full film elastohydrodynamic lubrication of the rolling linear guide under different operating conditions, enabling self-lubrication and maintenance-free operation of the rolling linear guide. This research aims to provide a reference basis for the preparation and use of self-lubricating rolling linear guides.